Bio- Social Determinants Of Birth Weight In Rural Urban Nagpur - Gawande U.H; Pimpalgaonkar M.S; Bethariya S.H (Wolters Kluwer Medknow Publications, 1994)
Research Questions: What are the bio â€" social determinants of birth weight of babies born in an urban- rural area? Objectives: 1. To study the biosocial determinants of birth weight 2. To determine which of the these affects birth weight. Design : Cross- sectional study. Setting : General hospital in Nagpur Participants: Mothers and their babies who were delivered in hospital. Study Variables : Motherâ€s age, parity, inter- pregnancy interval, socio-economic status, literacy status, antenatal care. Outcome Variable: Birth weight of the Infant. Statistical Analysis: Chi square test. Results: The proportion of low birth weight babies was high in teenage mothers(41.9%) and those over the age of 30 years. Primi and grand multiparity were associated with higher prevalence of low birth weight babies (43.2% & 43.9% respectively). Interpregnancy interval of less than one and a half years had a high prevalence of LBW babies (44.7%) but an interval of 5 years was also a risk as there were other associated risk factors like secondary sterility, tuberculosis etc. Low socio-economic status and low literacy levels were associated with significant proportion of LBW babies. Those mothers who had received adequate antenatal care gave birth to a significantly lower proportion of LBW babies than those who has not received antenatal care. Conclusion: Birthweight is determined by biosocial factors which are recognisable and some of which can be controlled.